2011
DOI: 10.1007/s00449-011-0560-9
|View full text |Cite
|
Sign up to set email alerts
|

Ionization constants and solubility of compounds involved in enzymatic synthesis of aminopenicillins and aminocephalosporins

Abstract: The article deals with experimental determination of ionization constants and solubility for the compounds (target products, initial β-lactams, acylating agents and by-products) involved in enzymatic synthesis of some therapeutically used aminopenicillins and aminocephalosporins, namely ampicillin, amoxicillin, cephalexin, cephadroxil, cephaloglycin, cefaclor, cefprozil, cefatrizine. Methodology of investigations and the evaluation of experimental data for the determination of ionization constants and solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…59 Others sources report different values for the isoelectric points, calculated on the basis of the dissociation constants evaluated in the respective study. 56,60,61 Partition and Distribution Coefficient Clarke's Analysis of Drug and Poisons reports an octanol/water coefficient (log P) for cephalexin of 0.6, which is similar to values from other sources (Drug Bank: prediction with ALOGPS program: 0.55; Hazardous Substances Data Bank: Hansch, Leo et al: 0.65). 55,62,63 Davis and Papich et al reported a log P of À1.12 64 while Kasim et al published a log P of À0.67 and a Clog P of À1.64.…”
Section: Isoelectric Point and Pk Asupporting
confidence: 56%
“…59 Others sources report different values for the isoelectric points, calculated on the basis of the dissociation constants evaluated in the respective study. 56,60,61 Partition and Distribution Coefficient Clarke's Analysis of Drug and Poisons reports an octanol/water coefficient (log P) for cephalexin of 0.6, which is similar to values from other sources (Drug Bank: prediction with ALOGPS program: 0.55; Hazardous Substances Data Bank: Hansch, Leo et al: 0.65). 55,62,63 Davis and Papich et al reported a log P of À1.12 64 while Kasim et al published a log P of À0.67 and a Clog P of À1.64.…”
Section: Isoelectric Point and Pk Asupporting
confidence: 56%
“…This upper concentration in this range could potentially affect permeability. However, the Carmellose sodium HU( 1 ) NL 23.2-160 Cellulose, microcrystalline BE( 3 ) CZ( 4 ) DE( 5-7 ) DK( [8][9][10][11] ) ES( [12][13][14][15][16] ) FI( [17][18][19] ) FR( [20][21][22] ) HR( 23 ) HU( 1,24 ) IE( 25 ) IS( 26,27 ) IT( [28][29][30][31][32] ) NL( 2,33 ) NO( 34,35 ) PT( [36][37][38][39] ) RO( [40][41][42] ) SE( 43,44 ) SK 45 [12][13][14][15][16]55,56,[68][69][70] ) FI( [17]…”
Section: Effect Of Excipients and Manufacturing Variationsmentioning
confidence: 99%